2015
DOI: 10.1523/jneurosci.0319-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity of Insula, Basal Ganglia, and Prefrontal Executive Control Networks during Hypoglycemia in Type 1 Diabetes

Abstract: Human brain networks mediating interoceptive, behavioral, and cognitive aspects of glycemic control are not well studied. Using group independent component analysis with dual-regression approach of functional magnetic resonance imaging data, we examined the functional connectivity changes of large-scale resting state networks during sequential euglycemic-hypoglycemic clamp studies in patients with type 1 diabetes and nondiabetic controls and how these changes during hypoglycemia were related to symptoms of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 44 publications
6
42
1
Order By: Relevance
“…As the brain is reliant on glucose for metabolism, the effect of dysglycemia on brain development and functioning is an area of physiological and clinical interest (1). Several previous studies have found that individuals diagnosed with T1D at a younger age (∼4 years) may be at a greater risk for developing neuropsychological deficits at later ages (2–4).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the brain is reliant on glucose for metabolism, the effect of dysglycemia on brain development and functioning is an area of physiological and clinical interest (1). Several previous studies have found that individuals diagnosed with T1D at a younger age (∼4 years) may be at a greater risk for developing neuropsychological deficits at later ages (2–4).…”
Section: Introductionmentioning
confidence: 99%
“…(1). Thus, different brain functional units must coordinate as networks to mediate the cognitive and behavioral aspects associated with dysglycemia (1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations